Follow-up of Neonatal Ovarian Cysts. A Retrospective Cross-sectional Study - Didem Baskin Embleton; Betul Zengin; Ahmet Ali Tuncer; Ahmet Afşin Kundak; Evrim Ozkaraca Boyaci; Salih Çetinkurşun (National Scientific Medical Center, 2019)
Objective: This study was planned to see the results of follow-up of ovarian cysts in newborn patients at a university hospital. Methods: Newborns with ovarian cysts that were diagnosed by US between 2010 and 2018 were retrospectively evaluated. US follow-up was performed in 2 to 3 month periods. Initial largest diameter of the ovarian cyst, number of cysts, bilateral or unilateral localization, if the cyst is complex or simple, alpha fetoprotein and β-HCG levels, if operated the type of the operation and pathology results were retrieved. Results: Nineteen patients were included. Seven patients had ovarian cysts ≥20 mm and 5 were complex cysts. Two of 5 complex cysts were operated for abdominal mass and ovarian torsion was diagnosed. Other 3 complex cysts are having a conservative treatment due to lack of any clinical symptoms. All regressed in size. All simple cysts had non-operative management and regressed in size during follow-up. AFP levels were high in all. Control AFP levels decreased in all patients. Conclusion: Conservative management seems appropriate for patients both with complex or simple cysts, because nearly all cysts were regressed and both ovaries persisted during follow-up. Surgical decision was the clinical presence of a mass in complex cysts. This is a small series and follow-up is short to make a final decision for management. A consensus is needed among the surgeons about the treatment options after discussing the complications related to conservative and surgical approaches of complex ovarian cysts.